2006
DOI: 10.1038/sj.jhh.1002107
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of one or two missed doses on the duration of action of combined perindopril and indapamide

Abstract: To evaluate the persistence of the antihypertensive effect of perindopril 4 mg þ indapamide 1.25 mg once daily for up to 72 h using the 'missed-dose' technique. Hypertensive patients were initially treated with perindopril 2 mg þ indapamide 0.625 mg once daily. After 4 weeks, the 135 of 216 patients who still had a diastolic BPX85 mm Hg went on to receive perindopril 4 mg þ indapamide 1.25 mg daily for a further 8 weeks. During either week 9 or 11, placebo was substituted for perindopril 4 mg þ indapamide 1.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A number of observational studies have consistently identified a higher risk of falling following antihypertensive medication initiation or titration 7–12. Patients with poor medication adherence, specifically poor implementation of antihypertensive pharmacotherapy, characterised by gaps in antihypertensive medication use, may experience a gradual rise in blood pressure 27–29. On resumption of therapy, similar to initial use, patients may be at a greater risk for falls relative to those who do not have gaps in antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of observational studies have consistently identified a higher risk of falling following antihypertensive medication initiation or titration 7–12. Patients with poor medication adherence, specifically poor implementation of antihypertensive pharmacotherapy, characterised by gaps in antihypertensive medication use, may experience a gradual rise in blood pressure 27–29. On resumption of therapy, similar to initial use, patients may be at a greater risk for falls relative to those who do not have gaps in antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacy dispensing records are an objective and indirect measure of medication adherence 35 36. We chose a 5-day gap based on the literature describing the gradual decline of the antihypertensive medication effect on blood pressure over 3 days,27–29 extending this period to 5 days due to the indirect method of adherence measurement, and to allow for potential variation in antihypertensive medication pharmacology 37. The number of occasions when gaps of 5 days occurred between sequential supplies during the previous 12 months was evaluated at baseline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small loss in ambulatory BP-lowering effect of 1.0/0.7 mm Hg with aliskiren in the 24-48-h period relative to the 0-24-h period compares favourably not only with that observed with irbesartan (3.6/2.2 mm Hg) or ramipril (4.0/2.6 mm Hg) in this study, but also with that observed with other antihypertensive drugs in previous studies. [10][11][12][13] Although comparisons across different studies must be interpreted with caution, the only other study that has reported a p1 mm Hg loss of 24-h ambulatory SBP/DBP-lowering effect in the 24-48-h postdose period relative to the 0-24-h period involved amlodipine, 10 an agent well known for its long duration of action. This study also used a simulated non-adherence phase, involving morning and evening self-measurement of BP by patients at home, to Sustained BP reduction beyond 24 h with aliskiren P Palatini et al evaluate BP-lowering effects up to 72 h after dose (that is, following two successive simulated missed doses of treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an office DBP>85 mmHg at week 4 had the dose increased to perindopril 4 mg+indapamide 1.25 mg daily. These patients were investigated in a separate study on the duration of the antihypertensive effect of perindopril 4 mg+indapamide 1.25 mg reported elsewhere (7). Patients with an office DBPv85 mmHg at week 4 were continued on perindopril 2 mg+indapamide 0.625 mg daily.…”
Section: Methodsmentioning
confidence: 99%